The intergenerational transmission of socioeconomic inequality through school and neighborhood processes. Issue 2 (3rd July 2019) - Coley, Rebekah Levine; Sims, Jacqueline; Thomson, Dana; Votruba-Drzal, Elizabeth
ABSTRACT: Both the prevalence and the repercussions of economic inequality have grown, heightening the need to delineate processes through which inequality is passed to the next generation. Assessing a nationally representative sample followed from adolescence through early adulthood (Add Health; N  = 18, 230), we tested a conceptual model hypothesizing that neighborhood and school resources, social norms, and stress would serve as mediating processes linking family socioeconomic resources with young adult education, employment, and earnings. Multilevel structural equation models suggest that family socioeconomic resources promote young adult educational and employment success in large part through adolescents' access to socioeconomically advantaged classmates and school social norms supportive of educational success. Neighborhood socioeconomic resources were a less consistent mediator between family resources and early adult socioeconomic success, whereas neighborhood norms and school and neighborhood stress did not serve as significant mediating processes. Results highlight the role of school (and to a lesser extent, neighborhood) contexts in the intergenerational transmission of inequality.